Loss of CTLH component MAEA impairs DNA repair and replication and leads to developmental delay - Hough, Søren; Jhujh, Satpal S.; Awwad, Samah W.; Lewis, Oliver E.; Lam, Simon; Thomas, John C.; Mosler, Thorsten; Bader, Aldo; Bartik, Lauren; McKee, Shane; Amudhavalli, Shivarajan; Colin, Estelle; et al. (EMBO molecular medicine, 2026)
Ubiquitin E3 ligases play crucial roles in the DNA damage response (DDR) by modulating the turnover, localization, activation, and interactions of DDR and DNA replication proteins. We performed a CRISPR-Cas9 knockout screen focused on ubiquitin E3 ligases and related proteins with the DNA topoisomerase I inhibitor camptothecin. This led us to establish that MAEA, a core subunit of the CTLH E3 ligase complex, is a critical regulator of homologous recombination and the replication stress response. In tandem, we identified eight patients with variants in MAEA who present with a neurodevelopmental disorder that we term DIADEM (Developmental delay and Intellectual disability Associated with DEfects in MAEA). Analysis of patient-derived cell lines and mutation modeling reveal an underlying defect in HR-dependent DNA repair and replication fork restart and protection as a likely cause of disease. Mechanistically, we find that MAEA dysfunction hinders DNA repair by reducing the efficiency of RAD51 loading at sites of DNA damage, which we propose may contribute to the presentation of DIADEM by compromising genome integrity and cell division during development.